Overproduction of the membrane-bound [NiFe]-hydrogenase in Thermococcus kodakarensis and its effect on hydrogen production - Kanai, Tamotsu; Simons, Jan-Robert; Tsukamoto, Ryohei; Nakajima, Akihito; Omori, Yoshiyuki; Matsuoka, Ryoji; Beppu, Haruki; Imanaka, Tadayuki; Atomi, Haruyuki (Frontiers in Microbiology, 2015)
The hyperthermophilic archaeon Thermococcus kodakarensis can utilize sugars or pyruvate for growth. In the absence of elemental sulfur, the electrons via oxidation of these substrates are accepted by protons, generating molecular hydrogen (H2). The hydrogenase responsible for this reaction is a membrane-bound [NiFe]-hydrogenase (Mbh). In this study, we have examined several possibilities to increase the protein levels of Mbh in T. kodakarensis by genetic engineering. Highest levels of intracellular Mbh levels were achieved when the promoter of the entire mbh operon (TK2080-TK2093) was exchanged to a strong constitutive promoter from the glutamate dehydrogenase gene (TK1431) (strain MHG1). When MHG1 was cultivated under continuous culture using pyruvate-based medium, a nearly 25 % higher specific hydrogen production rate (SHPR) of 35.3 mmol H2 g-dcw-1 h-1 was observed at a dilution rate of 0.31 h-1. We also combined mbh overexpression using an even stronger constitutive promoter from the cell surface glycoprotein gene (TK0895) with disruption of the genes encoding the cytosolic hydrogenase (Hyh) and an alanine aminotransferase (AlaAT), both of which are involved in hydrogen consumption (strain MAH1). At a dilution rate of 0.30 h-1, the SHPR was 36.2 mmol H2 g-dcw-1 h-1, corresponding to a 28 % increase compared to that of the host T. kodakarensis strain. Increasing the dilution rate to 0.83 h-1 resulted in a SHPR of 120 mmol H2 g-dcw-1 h-1, which is one of the highest production rates observed in microbial fermentation.